Multiple Family SES Indices: Variations between Middle Class and Lower Social Class Undergraduate Samples - Melissa Lopez Reyes (Social Work & Society, 2016)
In the face of socioeconomic hardships, social work programs for youth have been targeting not only the lower social class but also the middle class.  To address the need for socioeconomic status (SES) screening of prospective program beneficiaries, family SES indices were constructed for two largely middle-class undergraduate samples and a socioeconomically disadvantaged working-student sample from the Philippines.  Indices were constructed for assets, housing and appliances, perceived financial difficulties, financially-draining life circumstances, and financing.  Loadings resulting from nonlinear principal component analysis served as bases for reducing the indicators for an index.  The resulting indices for the middle and lower social class samples largely differ in their indicators and underlying factor, reflecting the different extent and patterns of socioeconomic adversity.  The indices for the middle class sample distinguish between objective indicators and perceived financial difficulties.  The indices for the lower social class reflect a pervasive and multidimensional experience of socioeconomic adversity. -- Resumen y Palabras clave: El estatus socioeconómico Familiar (SES) sirve como criterio fundamental en la selección de beneficiarios de los programas de asistencia social para los jóvenes. Los jóvenes son una fuente conveniente de información, aunque pueden no conocer ciertos detalles acerca de las finanzas (por ejemplo, los ingresos de los padres o los préstamos) de sus familias. Por lo tanto, los índices de SES en base a los informes de los jóvenes deben construirse claramente desde índices basados en los informes de los adultos. En este trabajo, cinco índices de SES (activos, vivienda, dificultades financieras, circunstancias vitales que afectan financieramente a la familia, y financiación) se calcularon por separado para tres muestras de jóvenes filipinos: dos muestras a estudiantes de grado en general y una muestra a estudiantes que trabajaban y que sufrían desventaja económica.  Los índices SES se calcularon utilizando análisis de componentes principales no lineales y también se examinó su estructura factorial. Los índices y los factores subyacentes fueron similares para las dos muestras generales aunque difirieron para los jóvenes de la muestra con desventajas socioeconómicas. Estos resultados sugieren la necesidad de criterios flexibles en el SES para su inclusión en los programas de asistencia social. La disponibilidad de diversos indicadores de SES, sin embargo, facilitaría la construcción de criterios flexibles dependientes de la población. Palabras clave: SES familiar, clase media, los jóvenes empleados, Filipinas.